The susceptibility of eighteen chrysanthemum cultivars to the chrysanthemum leaf miner, Phytomyza syngenesiae (hardy) - Ibrahim, Abdul Ghani; Madge, D. S. (Wiley-Blackwell Publishing, 1977)
Eighteen cultivars of indoor chrysanthemums were tested in the laboratory for susceptibility to adult female Phytomyza syngenesiae (Hardy). Host susceptibility was assessed by the density of feeding punctures, the density of eggs laid, and the amount of leaf damaged by the mining larvae. Eight of the cultivars were also tested in the field for their susceptibility to leaf damage. Cv. Mary Poppins, a ‘Mini-mum’, was the most susceptible, for it had most feeding punctures and most eggs per unit area, the largest percentage of mined leaves and a large percentage of damaged leaf area. Cv. Thumbelina, also a ‘Mini-mum’, was the least susceptible to leaf damage, for it had the smallest percentage of damaged leaf area, although a large number of the leaves were mined. Feeding puncture/egg ratios were not found to be a consistently reliable indicator of susceptibility.